Resistant Convulsion Due to Emergent Hipocalsemia Dependent Upon Antiepileptic Treatment (Annals of Medical Research, 2021)
None
Keywords: Hipocalcemia; Antiepileptic Drugs; Emergency Department; Convulsion.